Effect of calcium nitrate addition on growth and bulb quality of Hippeastrum - S. Ruamrungsri (2018)
© 2017, International Society for Horticultural Science. All rights reserved. Calcium plays an important role as cell wall component and relates to the tissue firmness because of its interaction with pectin of cell wall. In an attempt to improve the Hippeastrum ‘Apple Blossom’ bulb quality, the effect of calcium nitrate concentration was investigated. A field experiment was conducted with five calcium nitrate solutions i.e., 0, 50, 100, 150 and 200 mg L -1 . The experimental design was completely randomized design with three replications per treatment (10 plants replication -1 ). The results showed that at bulbs harvest stage (32 weeks after planting; WAP), applying additional calcium nitrate significantly affected the number of leaves per plant and leaf length of Hippeastrum. Plant supplied with calcium nitrate at 150 and 200 mg L -1 treatments gave higher results in the number of leaves per plant than plant supplied with calcium nitrate at 0 and 50 mg L -1 treatments. Bulb quality in terms of bulb fresh weight and root length was affected by treatments; while, bulb size (bulb circumference) and bulb firmness was not different among treatments. In addition, the concentration of nitrogen, phosphorus, potassium and total nonstructural carbohydrate (TNC) in bulb are discussed in this study.